The spiritual weakness of Western Missionary Founded Churches as the cause of the rise of Africa Independent Churches in Zimbabwe with special reference to theUniting Presbyterian Church in Southern Africa - Duncan, Graham A (University of Pretoria, 2014)
Dissertation (MA Theol)--University of Pretoria, 2013.